2015
DOI: 10.3390/md13085187
|View full text |Cite
|
Sign up to set email alerts
|

Hormaomycins B and C: New Antibiotic Cyclic Depsipeptides from a Marine Mudflat-Derived Streptomyces sp.

Abstract: Alterations in microbial culture conditions may trigger the production of diverse bioactive secondary metabolites. While applying various culture conditions and monitoring secondary metabolite profiles using LC/MS, hormaomycins B and C (1 and 2) were discovered from a marine mudflat-derived actinomycete, Streptomyces sp., collected in Mohang, Korea. The planar structures of the hormaomycins, which bear structurally-unique units, such as 4-(Z)-propenylproline, 3-(2-nitrocyclopropyl)alanine, 5-chloro-1-hydroxypy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…was the source of the hormaomycins B 155 and C 156, which each contain the unusual structural features (4Z)-propenyl-proline, 3-(2-nitrocyclopropyl)-alanine, 5-chloro-1-hydroxypyrrol-2-carboxylic acid and 3-methylphenylalanine only found before in hormaomycin. 106,107 A further mud-at Streptomycete produced the dilactonetethered, pseudo-dimeric peptides mohangamide A 157 and B 158. Apart from the dilactone-tethering, another interesting feature of these metabolites was the acyl chain-bearing dihydropyridine.…”
Section: Introductionmentioning
confidence: 99%
“…was the source of the hormaomycins B 155 and C 156, which each contain the unusual structural features (4Z)-propenyl-proline, 3-(2-nitrocyclopropyl)-alanine, 5-chloro-1-hydroxypyrrol-2-carboxylic acid and 3-methylphenylalanine only found before in hormaomycin. 106,107 A further mud-at Streptomycete produced the dilactonetethered, pseudo-dimeric peptides mohangamide A 157 and B 158. Apart from the dilactone-tethering, another interesting feature of these metabolites was the acyl chain-bearing dihydropyridine.…”
Section: Introductionmentioning
confidence: 99%
“…[46]; a new aromatic butyrolactone flavipesin A (31), isolated from a marine-derived endophytic fungus Aspergillus flavipes [47]; new non-cytotoxic lipopeptides gageopeptides A-D (32,33,34,35) [48] and gageotetrins A-C (36,37,38) [49], isolated from a Korean marine-derived Bacillus subtilis strain 109GGC020; a new cyclic depsipeptide hormaomycin B (39), isolated from a Korean marine mudflat-derived actinomycete Streptomyces sp. strain SNM55 [50]; a new glycolipid ieodoglucomide C (40) from the Korean marine-derived bacterium Bacillus licheniformis strain 09IDYM23 [51]; a new polycyclic tetramic acid macrolactam isoikarugamycin (41) from Equatorial Guinean Streptomyces zhaozhouensis strain CA-185989 [52]; a bromopyrrole alkaloid keramadine (42), isolated from the Okinawan marine sponge Agelas sp. [53]; "unprecedented" 9,11 secosterols with "the 2-ene-1,4-dione moiety" (43,44) from the Korean marine sponge Ircinia sp.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…In addition to hormaomycin, two other natural analogues, namely hormaomycin B and C, were isolated from a marine mudat-derived Streptomyces strain SMN55 collected in Mohang, Korea. 68 These analogues were accompanied by hormaomycin, which indicated that they were only side-products of hormaomycin biosynthesis arising from the omission of methylation at one phenylalanine residue and its incorporation instead of (b-Me)Phe.…”
Section: Hormaomycinmentioning
confidence: 99%
“…Their antibacterial activities have only been reported against a few bacterial strains. 68 They were generally 4-32 times weaker than hormaomycin, which indicates an important role for the methyl groups on the phenylalanine residues for the antibacterial potency of these compounds. 68…”
Section: Hormaomycinmentioning
confidence: 99%